As interações da cultura midiática na escola - Pirola, Maria Nazareth Bis (2015)
Investigates media culture interactions at school. Problematizes the high level of media consumption nowadays and justifies the necessity of research projects that accomplish to understand the meanings of this web of interactions, specially, the meaning construction, in act, involving children, teenagers and media culture. Adopts sociosemiotics as a theoreticalmethodological framework based on the works of Algirdas Julien Greimas, Eric Landowski, Ana Claudia Oliveira and their collaborators. Chooses a public elementary school at Jardim Camburi, Vitoria/Espirito Santo, as its locus and subject of study. Proposes an exploratory, descriptive and sociosemiotic research as its methodological procedure, qualitative data analysis, and methodological contribution of participant observation, conversation, in-depth interview and semiotic research. Uses research log and photographs as data collection instruments. Contributes to understanding meaning construction, in act, between children, teenagers and media culture, and presents suggestions of constructive dialogue that could be promoted by school community.